2015
DOI: 10.1016/j.foreco.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of ground-dwelling assemblages during reforestation with native oak depends on the mobility and feeding habits of the species

Abstract: HighlightsWe studied the recovery of ground beetles and millipedes during reforestation. We found no differences in species richness of forest carabids after canopy closure. The species richness of forest millipedes was the highest in the mature forest. Ground beetles recovered after the closure of canopy, while millipedes did not. Stenotopic forest species associated with microhabitats did not recover. the quantitative character species analysis also confirmed that reforestation with native oak after 51 mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 54 publications
3
67
0
Order By: Relevance
“…The rove 379 beetle assemblages of the samples from the native oak 380 plantation and red oak plantation were similar to each other 381 (stress value: 0.2516; Fig. 3 (Magura et al 2015). These treatments eliminate 398 the specific microsites and considerably alter the habitat 399 structure and microclimatic conditions, causing shift in the 400 ground-dwelling beetle assemblages (Magura et al 2006; 401 Roberge and Stenbacka 2014).…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…The rove 379 beetle assemblages of the samples from the native oak 380 plantation and red oak plantation were similar to each other 381 (stress value: 0.2516; Fig. 3 (Magura et al 2015). These treatments eliminate 398 the specific microsites and considerably alter the habitat 399 structure and microclimatic conditions, causing shift in the 400 ground-dwelling beetle assemblages (Magura et al 2006; 401 Roberge and Stenbacka 2014).…”
mentioning
confidence: 86%
“…71 Several studies revealed that reforestation has significant 72 effects on ground-dwelling arthropods (Finch 2005;73 Magura et al 1997;Niemelä et al 1993). In particular the 74 direct destruction of original habitats by intensive pre-and 75 post-treatments (clear-cutting, grubbing, tilling and deep 76 loosening) causes significant changes in the structure of 77 arthropod assemblages (Magura et al 2002(Magura et al , 2015. The 78 majority of published studies investigated the effects of 79 reforestation and accompanying forest managements on 80 ground beetles or spiders (Pohl et al 2007).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Ground beetles are excellent ecological indicators; numerous studies focused on their responses to urbanization and human disturbance (5,6). Most of the papers concentrate on the assemblages, and do not examine the populations and/or individuals, but see (7).…”
mentioning
confidence: 99%